The impact of nationality diversity on financial performance among manufacturing companies listed on the Indonesia Stock Exchange - Mardiyati, Umi; Siregar, M Edo Suryawan (Global Advances in Business Studies, 2022)
This study aimed to determine the effect of commissioner nationality on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange from 2015–2017. The results (after controlling for gender, board size, firm size, leverage, and liquidity) show that the presence of foreign commissioners on the board of commissioners does not significantly affect companies’ financial performance. A robustness test confirmed the regression results.